Interactive effects of phosphorus and potassium on biomass production and accumulation of nitrogen in field grown mungbean (Vigna radiata L.) (International Journal of Agricultural Research, Innovation and Technology, 2019)
A field experiment was carried out in the paddy field of Charfession Govt. College, Bhola, Bangladesh during rabi season 2017 to evaluate growth, biomass production and nitrogen accumulation in mungbean plants. The size of the plot was 60 cm x 45 cm. The distance between row to row and plant to plant was 30 cm and 10 cm, respectively. Eight plants were raised per plot. Seven treatments were P0K0 (Control), P5K6, P5K12, P5K18, P10K6, P10K12 and P10K18 kg ha-1. Forty day old plants were harvestedas root, stem and leaf. The highest plant height (17.2 cm) and number of leaves (14.3 no. plant-1) were recorded in P5K12 kg ha-1 treatment at harvest. The maximum concentration of nitrogen in root, stem and leaf were 1.59, 2.51 and 3.82% in the treatments of P5K12, P5K12 and P5K18 kg ha-1, respectively. The highest amount of dry matter yield 1.88 g plant-1 was observed in P5K12 kg ha-1 treatment. The overall better dose was P5K12 kg ha-1. Thus, a considerable amount of nitrogen and organic matter might be added to paddy fields through the cultivation of mungbean in the coastal region of Bangladesh.Int. J. Agril. Res. Innov. & Tech. 9 (1): 14-17, June, 2019